1993
DOI: 10.1002/jcb.2400510402
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of electromagnetic fields

Abstract: Selective control of cell function by applying specifically configured, weak, time-varying magnetic fields has added a new, exciting dimension to biology and medicine. Field parameters for therapeutic, pulsed electromagnetic field (PEMFs) were designed to induce voltages similar to those produced, normally, during dynamic mechanical deformation of connective tissues. As a result, a wide variety of challenging musculoskeletal disorders have been treated successfully over the past two decades. More than a quarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
142
0
7

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(152 citation statements)
references
References 14 publications
3
142
0
7
Order By: Relevance
“…Physical factors such as mechanical, electrical, and magnetic stimulation exhibit anabolic action on bone formation (Bassett 1993;De Mattei et al 1999;Vander Molen et al 2000;McLeod and Collazo 2000). Static magnetic field (SMF) has been used advantageously in various orthodontic treatments (Noar and Evans 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Physical factors such as mechanical, electrical, and magnetic stimulation exhibit anabolic action on bone formation (Bassett 1993;De Mattei et al 1999;Vander Molen et al 2000;McLeod and Collazo 2000). Static magnetic field (SMF) has been used advantageously in various orthodontic treatments (Noar and Evans 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that extremely low frequency electromagnetic fields (ELFEMFs) can exert influences on biological functions of cells and tissues. These effects include bone healing [Basset, 1983], nerve regeneration [Kim et al, 2002], influences on cell calcium levels [Walleczek et al, 1999] and oncogene activation [Lagroye and Poncy, 1998]. On the contrary, the most part of studies concerning genotoxic effects were negative [Vijayalaxmi and Obe, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…[11] The application of external electrical or mechanical energy may affect disorders of dense connective tissue with induces changes to the cell environment. [12][13][14] Results of several studies have shown that exposure to EMFs was effective in reducing pain and edema after soft tissue injury. They suggested that exposure to EMF may affect at cellular, and neurobiological level and reduce pain sensitivity and pain inhibition.…”
Section: Introductionmentioning
confidence: 99%